2011
DOI: 10.1007/s10965-011-9756-6
|View full text |Cite
|
Sign up to set email alerts
|

Particular thermal properties of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) oligomers

Abstract: Telechelic hydroxylated poly(3-hydroxybutyrateco-3-hydroxyvalerate)s (PHBV-diols) were synthesized by transesterification with ethylene glycol, which could be used as the macromonomers for synthesis of block copolymers. PHBV-diols owned particular thermal properties. PHBV-diols had much lower the melting temperatures (T m s) and better thermal stability than original PHBV. With the decrease of molecular weight, T m s of PHBV-diols decreased gradually and maximum degradation temperatures (T max s) increased gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
6
0
2
Order By: Relevance
“…It can be seen from Table 1 [52] that the melting temperature of commercial P(3HB-co-3HV) was beyond 150 ∘ C. In addition, P(3HB) and P(3HB-co-3HV) were unstable above 160 ∘ C mainly by nonradical, random chain scission (cis-elimination) reaction, which resulted in a drastic reduction in molecular weight during melt processing. Therefore, the melt processing window of P(3HB) and P(3HB-co-3HV) was narrow [2,62]. P(3HB) and P(3HB-co-3HV) are brittle materials, which makes them unsuitable for some applications.…”
Section: Drawbacksmentioning
confidence: 99%
“…It can be seen from Table 1 [52] that the melting temperature of commercial P(3HB-co-3HV) was beyond 150 ∘ C. In addition, P(3HB) and P(3HB-co-3HV) were unstable above 160 ∘ C mainly by nonradical, random chain scission (cis-elimination) reaction, which resulted in a drastic reduction in molecular weight during melt processing. Therefore, the melt processing window of P(3HB) and P(3HB-co-3HV) was narrow [2,62]. P(3HB) and P(3HB-co-3HV) are brittle materials, which makes them unsuitable for some applications.…”
Section: Drawbacksmentioning
confidence: 99%
“…Moreover, commercial PHBHV shows some disadvantages, such as poor thermal stability and high melting temperature. PHBHV´s thermal degradation temperature is close to 160°C and their melting temperature is around 150°C, resulting in a small processing window [39].…”
Section: Why Phb and Phbhv Need Modifications?mentioning
confidence: 99%
“…Liu,Q. et al [39] synthesized telechelic PHBHV-diols with various molar mass by trans-esterification with ethylene glycol. The results showed that PHBHV-diol was more stable than original PHBHV and the melt-processing window increase gradually with molar mass decrease.…”
Section: Molar Mass Reduction and Further Modificationsmentioning
confidence: 99%
“…Esse fenômeno de redução da T m com a inserção de hidroxilas terminais e diminuição da massa molar também foi observado por Liu et al (2012) (DAGNON et al, 2009). Após a análise do efeito dos parâmetros do processo de síntese de nanopartículas de PHBHV no diâmetro hidrodinâmico e índice de polidispersidade, realizou-se o estudo da estabilidade das dispersões dessas partículas ao longo do tempo.…”
Section: Espectroscopia De Infravermelho Por Transformada De Fourier unclassified
“…De acordo com os autores, a redução nos valores de T m foi consequência da redução na perfeição dos cristais do PHBHV-diol.Além das diferenças nos valores obtidos para as T m , no termograma do PHBHVdiol, o primeiro pico de fusão ficou mais evidente, quando comparado com o PHBHV (M n = 121kDa, Ð= 1,90), como pode ser observado pela Figura 9 e pelo valor da entalpia de fusão (ΔH m1 ) da Tabela 3, que se relaciona com o valor da área do pico. Esse resultado também foi obtido porLiu et al (2012). Os autores concluíram que isso ocorreu, pois, o PHBHV-diol possui maior concentração de grupos terminais hidroxila.…”
unclassified